Central nervous system involvement in goats undergoing primary infections with Trypanosoma brucei and relapse infections after chemotherapy - Whitelaw, D.D.; Moulton, J.E.; Morrison, W. Ivan; Murray, M. (Cambridge University Press, 1985)
Relapse of infection after trypanocidal drug treatment of trypanosome infections is normally attributed to drug resistance on the part of the parasite, under-dosage of the drug, or reinfection of the host. We have demonstrated relapse infections in goats arising from none of these. Fourteen goats infected withTrypanosoma bruceisuffered severe illness and 3 died within 45 days. Despite treatment with the trypanocidal drug Berenil, a 4th goat died 2 days later. Recovery of the remainder followed chemotherapy, and in 2 goats, necropsiecl 45 days after treatment, no trypanosomes or abnormalities were detected. However 2–3 months after Berenil chemotherapy, despite trypanosomes being undetectable in the blood during the intervening period, infections in 4 of the remaining 8 animals relapsed. At all stages of the primary and relapse infections, trypanosomes isolated from the blood of the goats were completely susceptible to Berenil when tested in mice, as were parasites isolated from cerebrospinal fluid and brain tissue at necropsy. At the time of treatment, only minimal cellular infiltration was found in the central nervous system (CNS), but death from the relapse infection was associated with a very severe meningoencephalitis. We conclude that the relapse infections were caused by the re-emergence of trypanosornes from the CNS, where sequestered parasites were inaccessible to the trypanocidal effects of the drug.